Outcome of survivors of COVID-19 in the intermediate phase of recovery: A case report - Marelee Fourie; Heleen van Aswegen (AOSIS, 2022)
Introduction: Coronavirus disease 2019 (COVID-19) is a viral respiratory disease and is associated with significant morbidity in the intermediate and chronic phases of recovery from the disease. The health benefits of respiratory and extremity muscle strengthening exercise therapy are well-described for those with cardiac failure and interstitial lung disease and are suggested to improve functional ability for patients recovering from COVID-19. The aim of this case report is to share the effects of standard physiotherapy management on exercise endurance, respiratory function and return to work, implemented for patients with COVID-19 in the intermediate phase of their recovery. Patient presentation: Two cases of COVID-19 were admitted to a private healthcare facility in Johannesburg. They presented with shortness of breath and decreased endurance. One had COVID-19 myocarditis and the other chronic post-COVID-19 organising pneumonia with pulmonary fibrosis. Management and outcome: Both patients were admitted to ICU, provided oxygen therapy and supportive care as well as physiotherapy management in hospital and after hospital discharge. Physiotherapy management included inspiratory muscle training therapy, and cardiovascular and resistance exercise therapy. Improvements in peak expiratory flow rate and six-minute walk distance were observed for both cases at 6- and 7-months follow-up, respectively. Conclusion: Our case report illustrates the value of ongoing physiotherapy management, utilising progressive exercise therapy prescription, to aid the return to optimal functioning for survivors of COVID-19 in the intermediate phase of their recovery.